SERVICE QUALITY, PRICE AND PRODUCT PROMOTION TOWARDS CUSTOMER TRUST, IMPACT ON CUSTOMER LOYALTY GRAB BIKE DEPOK REGION - Dian Riskarini; Yuli Ardianto (Kusuma Negara Business School, 2021)
Technological developments have offered solutions for the community in facing the level of congestion in Jabodetabek. Online transportation is one of the accesses that answer the phenomenon of people's need to be on time and get transportation options with various benefits, one of which is Grab Bike as a transportation service that is managed by an online system. This study was conducted to determine whether service quality, price and product promotion directly or indirectly affect customer trust and have an impact on customer loyalty Grab Bike Depok area. The population in this study was Grab Bike Depok customers with a sample size of 100 respondents using the Purposive Random Sampling technique. Using this type of quantitative research by analyzing respondents' primary data questionnaires. Data analysis techniques using the Path Analysis. The results of the study of service quality significantly influence customer trust where if the quality of service is getting better then Grab Bike customer trust will increase as well. Similarly, the variable price significantly influences customer trust. With better customer perceptions of the price of Grab Bike services, it will be able to increase the trust of Grab Bike customers. The promotion variable influences customer trust, with increasing promotion it will be able to increase the trust of Grab Bike customers. Service quality variables significantly influence customer loyalty. With better service quality, Grab Bike customers can increase customer loyalty. Price variable significantly influences customer loyalty. This means that applying the right price will increase Grab Bike customer loyalty. Promotional variables significantly influence customer loyalty. This means that with increased promotion, Grab Bike customers can increase loyalty. Based on the test results, it can be concluded clearly that Service Quality, Price and Promotion have a significant partial and simultaneous effect on the increasing trust of grab Bike customers in the Depok area and have an impact on customer loyalty to continue using Grab Bike online transportation services. Keywords: Service Quality, Price, Product Promotion, Customer Trust, Customer Loyalty